Pengaruh Good Corporate Governance dan Corporate Social Responsibilities terhadap Tindakan Pajak Agresif (Studi pada Perusahaan Manufaktur Sektor Aneka Industri yang Listing di BEI Tahun 2010-2014 - Rosita, Siti Ita; Febriawan, Febriawan (Institut Bisnis dan Informatika Kesatuan, 2018)
Good Corporate Governance (GCG) is a system that regulates and controls companies to create added value for all stakeholders in order to achieve companie’s objectives. The elements of GCG playing essential role in a company are the size of the Board of Commissioners, the size of the Board of Directors, and the size of institutional ownerships. Corporate Social Responsibility (CSR) is a form of company’s awareness towards its neighborhood through many events held in order to preserve the environments, development participation, and other forms of social responsibilities. CSR also one of the implementations of GCG concept carried out by companies. The application of GCG and CSR is an essential factor for share holder to invest their fund. Investor are more likely to be interested investing in companies where GCG and CSR are applied, this is mainly because the company’s control system and environmental preservation efforts are considered to be more profitable for both share and stakeholders. This research is purposed to investigate (1) the influence of the size of Board of Commissionerson aggressive tax conducts (2) the influence of the size of Board of Directors on aggressive tax conducts (3) the influence of institutional ownerships on aggressive tax conducts (4) the influence of CSR on aggressive tax conducts. The samples used are manufacturing companies from the various sector listed in Indonesia Stock Exchange in the period of 2010-2014. These samples are collected using purposive samplings. There are 14 sample companies match the research criteria. The research analysis used is multiple regression analysis using statistical software SPSS 22. The research resulted that the size of Board of Commissioners has no significant effect on the aggressive tax conducts. Meanwhil, the suze of the Board of Directors, the institutional ownerships and CSR have significant effect on aggressive tax conducts